2014
DOI: 10.1016/j.autneu.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus tractus solitarii A2a adenosine receptors inhibit cardiopulmonary chemoreflex control of sympathetic outputs

Abstract: Previously we have shown that stimulation of inhibitory A1 adenosine receptors located in the nucleus tractus solitarii (NTS) attenuates cardiopulmonary chemoreflex (CCR) evoked inhibition of renal, adrenal and lumbar sympathetic nerve activity and reflex decreases in arterial pressure and heart rate. Activation of facilitatory A2a adenosine receptors, which dominate over A1 receptors in the NTS, contrastingly alters baseline activity of regional sympathetic outputs: it decreases renal, increases adrenal and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…, ; Minic et al. 2014b). Adenosine is released into the NTS during life‐threatening situations such as ischemia, hypoxia, and severe hemorrhage (Winn et al.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…, ; Minic et al. 2014b). Adenosine is released into the NTS during life‐threatening situations such as ischemia, hypoxia, and severe hemorrhage (Winn et al.…”
Section: Introductionmentioning
confidence: 98%
“…A 1 receptors most likely inhibit glutamate release in the CCR network (Ichinose et al 2012). Our recent studies indicated that adenosine A 2a receptors inhibit CCR transmission in the NTS (Minic et al 2014b) and this inhibition occurs via a GABA-ergic mechanism (Minic et al 2015). A 2a adenosine mediated inhibition is markedly attenuated, that is, the CCR responses are restored following GABA-ergic blockade in the NTS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of peripheral A2A causes increased release of adrenergic neurotransmitters, 23 whereas activation of nucleus tractus solitarii A2A is reported to inhibit regional sympathetic and hemodynamic reflex responses. 24 In laboratory animals and in humans, regadenoson decreases systolic and diastolic blood pressures and causes an increase in heart rate. 8,23,25,26 Thus, the drop in blood pressure is usually countered by direct sympathoexcitation and an autonomically mediated elevation in heart rate that increases cardiac output and maintains adequate perfusion of vital organs.…”
Section: Asystolementioning
confidence: 99%